Concussion in sport: what is known and what is new? - Catharina Grant; Dina Janse van Rensburg; Audrey Jansen van Rensburg; Rob Collins (South African Family Practice)
The aim of this article was to summarise the latest definition of concussion, signs of concussion, as well as important facts on recovery and graduated return to play, for different age groups. New technologies available to the sports physician are listed.